Research and progress of laser cladding on engineering alloys: A review - Liu, Yanan; Ding, Ye; Yang, Lijun; Sun, Ronglu; Zhang, Tiangang; Yang, Xuejiao (Journal of manufacturing processes, 2021)
Engineering alloys are widely applied as important functional structural materials in aerospace, electronics, metallurgy, and other high-end engineering industries due to their superior properties. However, their further application remains notably restricted by numerous inherent limitations, including low hardness, terrible wear and high-temperature oxidation resistance. In response to this problem, the development of laser cladding (LC) technology has provided new approaches for surface modification of engineering alloys. In this review paper, the recent progress made in the preparation of engineering alloys by LC technology is thoroughly investigated. The elementary knowledge in this field is provided to establish the internal relationships among the laser processing parameters, microstructure, and significant mechanical properties. The LC processing methods and material systems are reviewed, and the critical functional coatings related to this field are also summarised and explored in detail. Furthermore, the current challenges and future efforts are presented, identifying the existing knowledge and technology gaps while also attempting to determine future research directions.